THE BEHAVIOR ANALYSIS OF DIGITAL VIDEO STORYTELLING ADVERTISEMENT AUDIENCE (Journal of Business and Management, 2021)
Digital or social media advertising is becoming trends in the world recently. The intense competition in industry is getting bigger, companies compete to get customer attention by creating advertisement that most of them have similar message. Therefore, in social media people see advertising as annoying things that will be skipped. One of the solutions is storytelling advertising which is have persuasive effect to influence consumer though storyline. So, this study aims to identify the behavior of the video storytelling advertisement audience in digital media especially social media where in the previous research shows that the story plays with consumer emotions and also influences consumer attitude and perception toward an object. Also, uses a quantitative approach through online questionnaires as tools to collect the the total sample use in this study is 419 samples. The results show that storytelling advertising can eliminate the negative emotions and generate more favorable emotional responses such as warm feelings compared with factual advertising. Humor and stories about daily life with meaningful messages are the type of storytelling advertising that get the most attention from viewers.Keywords: Video Storytelling advertisement, Behavior, Digital media, Customer emotion, Quantitative